Praeger guide to the psychology of gender - Paludi, Michele Antoinette (Praeger Publishers, 2004)
When we examine the field of gender psychology closely, we note that much of what the popular media tells us about women and men does not hold up to research scrutiny. This handbook helps to replace media stereotypes and myths with realities and shows us that there are more similarities between the sexes than differences. The contributors to this handbook have a highly practical and readable approach that will prompt readers to examine their self-awareness and social tolerance to biases against women and men in our social institutions such as schools and workplaces. They also reveal that the i.